Perceived Service Quality Toward Customer Satisfaction in Majlis Perbandaran Seremban - Rosnita Binti Sakarji, Siti; Binti Jamin, Aziean; Binti Ahmad, Nurbarirah; Mayang Delima Binti Mohd Beta, Raja; Binti Ismail, Shafinar; Binti Mohd Zain, Zainab (KnE Social Sciences, 2020)
This research was conducted on purpose to examine the internal customer satisfaction level through service quality of Majlis Perbandaran Seremban (MPS). A survey on internal customer satisfaction level through service quality was conducted among internal staff in MPS involving 260 respondents. The attributes of service quality such as reliability, assurance, responsiveness, tangible and empathy have been identified in order to investigate whether or not these factor have significant relationship with customer satisfaction. From this study, the researcher able to determine the current level of internal customer satisfaction that they perceive from service provided by Majlis Perbandaran Seremban (MPS), from this research the researcher has found that among the elements tangible has become the most significant relationship toward customer satisfaction. Keywords: internal customer, service quality, customer satisfaction